Letter - Watts, S. R.; Johnston, D. Hope (Douglas Hope) (1989)
Letter describing the background to the design of the Arthur Phillip memorial in 1931, commissioned by Douglas Hope-Johnston. The memorial was erected on an external wall of St. Mildred's Church, London, but was destroyed by bombing in World War II. Includes a rough sketch of the memorial design.
Manuscript reference no. : NLA MS 7812.
S.R. Watts was a draughtsman who designed a memorial to Admiral Sir Arthur Phillip in 1931.
Keywords: Watts, S. R. -- Correspondence; Phillip, Arthur, -- 1738-1814 -- Monuments -- England -- London; Arthur Phillip memorial (London, England); St. Mildred's Church (London, England); Architects -- Great Britain -- Correspondence; Memorials -- England -- London; Admirals -- Great Britain -- Monuments; Architects